Do (Should) Brokers Route Limit Orders to Options Exchanges That Purchase Order Flow? - Battalio, Robert; Griffith, Todd; Van Ness, Robert (Journal of Financial and Quantitative Analysis, 2021)
Abstract We examine whether options exchanges’ pricing schedules affect broker order routing behavior and limit order execution quality. We find that some brokers seemingly maximize the value of their order flow by selling marketable orders and sending nonmarketable orders to exchanges that offer large liquidity rebates. Other brokers appear to bypass liquidity rebates by routing both marketable and nonmarketable orders to exchanges that purchase order flow. Using a decision by the Philadelphia Stock Exchange (PHLX) to change its trading protocol, we provide empirical evidence that brokers can enhance limit order execution quality by routing nonmarketable limit orders to options exchanges that purchase order flow.